Internet addiction in adolescents in Central Siberia: analysis of prevalence and structure of consumed content - L. S. Evert; S. Yu. Tereshchenko; O. I. Zaitseva; N. B. Semenova; M. V. Shubina (Бюллетень сибирской медицины)
The aim of this study was to investigate the prevalence of Internet addiction (IА) and the structure of consumed content among adolescents in Central Siberia.Materials and methods. From January to May 2019, 3,012 adolescents (45.8% of boys and 54.2% of girls) aged 12–18 years were examined (average age 14.5 ± 1.3 years). Younger adolescents (12–14 years old) accounted for 52.5%, and seniors (15–18 years old) accounted for 47.5%. Peculiarities of online behavior were evaluated according to Chen’s Internet Addiction Scale (CIAS) adapted by V.L. Malygin and K.A. Feklisov; a  total CIAS score of ≥ 65 indicated Internet addiction. Gambling addiction was rated according to the Game Addiction Scale for Adolescents, and addiction to social networks was rated according to the Social Media Disorder Scale. The structure of the consumed content was estimated in the overall sample and in two age groups. The data obtained were processed by non-parametric statistical methods using the Statistica 12.0 software. Quantitative characteristics are presented as the median and the interquartile range Me (Q25 – Q75), binary signs are represented as a share (%) and the confidence interval. The significance of the  differences (p) for quantitative indicators was evaluated by Mann – Whitney U-test and for binary characters by Pearson’s χ2 criterion. The differences between the groups were considered statistically significant at p ≤ 0.05.Results. The overall prevalence of IА was 6.9%, adaptive use of the Internet was observed in 49.4% of adolescents, non-adaptive use was registered in 43.6% of cases. The frequency of Internet addiction increases with age: from 6.0% in 12–14 year-old adolescents to 8.0% in 15–18 year-old adolescents (p = 0.0324). Content consumed by adolescents included gambling addiction (11%), addiction to social networks (8.0%), mixed IA (2.6%), and undifferentiated Internet addiction (2.8%). Younger adolescents are more often dependent on online games (12.2%), social networks (9.3%), and mixed IА (3.3%), while in older adolescents, undifferentiated IА is more often observed (39.5%).Conclusion. High level of IA prevalence in adolescents in Central Siberia confirms the relevance of this problem and indicates the need to develop preventive measures aimed at maintaining child and adolescent health.